Transport function of transcobalamin II - Rappazzo, Mary E. (1972)
The uptake of free and bound (57)CoB(12), principally to transcobalamin II (TC II), was studied in isolated, perfused liver and kidney of the dog. (1) There was good uptake of canine TC II-B(12) by both organs. (2) In the liver TC II enhanced uptake over that of free B-12. (3) Renal uptake of free B-12 was greater than that of TC II-B(12). Free B-12 was neither lost in the urine nor returned to the circulation. (4) On a per gram tissue basis, renal uptake of TC II-B(12) was greater than hepatic. (5) There was renal release or production of TC II (6) Some TC II but more of a larger molecular size binder came from the liver. (7) Passing free B-12 through the kidney enhanced its uptake by the liver. (8) Passing free B-12 through the liver depressed its uptake by the kidney. (9) It is postulated that the distribution of B-12 can be modified by (a) different responses of tissue to TC II-B(12), (b) synthesis of TC II by an organ, and (c) the effects of B-12 passing through one organ to another.